Treatment of ovaries atrophy in heifen and cows. II By combining serum gonadotropin and chorionic gonadotropin hormones - ΣΕΪΤΑΡΙΔΗΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of ovaries atrophy treatment in heifeus and cows are given using 1000 I. U. serum gonadotropin and 1000 Human chorionic gonadotropin. 15 (55,5%) heifers out of 27 showed oestrus 21 days post injection and 10 (37,0%) conceived after the first insemination, beside 24 cows out of 34 (70,6%) showed oestrus 21 days post injection and 22 (64,7%) were pregnant after the first insemination. Totally 39 out of 61 heifus and cows (63,9%) showed oestrus 21 days post-injection and 31 (52,5%) conceived after the first insemination.